Analisis Pengaruh Kinerja Karyawan PT Jasa Marga (Persero) TBK Cabang Jagorawi - Nazwirman; Syamsu Alang; Agung Prianggodo (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this study was to determine whether there is an influence between work discipline, organizational culture on employee performance either partially or jointly in PT Jasa Marga (Persero) Tbk, Branch Jagorawi. Results of analysis that Work Discipline positive effect on employee performance, with a very strong degree of correlation values. influence the value of the (R) of 0.871, the contribution of the coefficient of determination (R2) of 0.759 or 75.9%. Organizational culture has a positive effect on employee performance, with a very strong degree of correlation values. influence the value of the (R) of 0.915, the contribution of the coefficient of determination (R2) of 0.838 or 83.8%. And Discipline of Work and Organisational Culture jointly have a positive influence on employee performance, with a very strong degree of correlation values. influence the value of the (R) of 0.920, the contribution of the coefficient of determination (R2) of 0.847 or 84.7% indicates the significance of the effect given by the Discipline of Work and Organizational Culture on Employee Performance. ANOVA analysis showed that the obtained value obtained Fvalue of 283.961 greater value to Ftable 3.940 at alpha (Î±) 5% = (267.551> 3.940) means there is a rejection of H0. It means that the variable labor discipline and organizational culture together significantly affect employee performance variables, and there is a very strong influence of the value stated.